Non-Compliance of Medication and Precipitating Factors Leading to Acute Heart Failure - Naveen, Maria; Ijaz ul Haq; Maroof Hassan; Uzair Aslam; Alam, Muhammad Iftikhar; Khan, Atif Ahmed (Indus Journal of Bioscience Research, 2025)
Objective: To evaluate medication non-compliance and its precipitating factors leading to acute heart failure among patients treated at the NICVD, Karachi, and identify socio-economic and demographic predictors of non-compliance. Methodology: A cross-sectional study was conducted on 207 patients aged 18–80 years at the NICVD from January to December 2023. Demographic data, compliance levels, and socio-economic factors were collected. Non-compliance was assessed through patient interviews and clinical records. Chi-square tests and regression analyses were performed to determine associations, with a significance threshold of p < 0.05. Results: Among the 207 patients, 60% were male, and the mean age was 55.3 years. Non-compliance was observed in 42% of patients, highest in the 40–60 age group (48%). Lower education (60% non-compliance in those below high school education, p = 0.03) and low income (50% non-compliance in low-income groups, p = 0.04) were significant predictors. Non-compliance was associated with increased hospital readmissions (57% vs. 35% in compliant patients, p = 0.01). Regression analysis showed that non-compliance likelihood increased by 2.5% per year of age, and patients with low literacy were 1.8 times more likely to be non-compliant. Conclusion: Medication non-compliance significantly impacts acute heart failure management, with socio-economic and demographic factors playing crucial roles. Strategies to improve health literacy and address financial barriers are essential to enhance adherence and reduce readmissions.